Implementation Place of ‘Uqubat Canings in Fiqh Perspective (Analysis of Aceh Governor Regulation Number 5 of 2018) - Helmi Helmi; Saiful Bahri; Riyandi Riyandi; Nurazizah Nurazizah; Nurmasyitah Nurmasyitah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
One form of the development of fiqh is to make the charge of fiqh in the form of theoretical laws into practical laws by putting them in the legislation of a certain State or territory in the State. After being granted the right to implement Islamic sharia by the State, Aceh as a provincial territory within the Unitary State of the Republic of Indonesia had the opportunity to realize fiqh laws into legislation termed Qanun, in order to regulate the behavior of its people to be under the auspices of sharia law. Throughout the course of the application of Islamic sharia based on various Qanun that was built, its implementation has never been separated from various problems and criticisms, both from the internal elements of Aceh, National and International. Among the cases that finally led to the problem was the birth of the Aceh PERGUB Number 5 of 2018. The problem that arose was a sharp criticism contents of some of the PERGUB contents which was deemed to deviate from the previous Qanun and deviated from the provisions of fiqh, even further claimed as an effort to dwarf the Islamic sharia. However, if examined objectively, it is not certain that the regulation will deviate from the existing Qanun and fiqh. But like a hot ball that is rolling, the debate that occurs in response to the PERGUB is sometimes no longer at the level of finding a solution, but it has led to things that are political.